Vitamin D composition of Australian foods - Dunlop, Eleanor; James, Anthony; Cunningham, Judy; Strobel, N.; Lucas, R.M.; Kiely, M.; Nowson, C.A.; Rangan, A.; Adorno, P.; Atyeo, P.; Black, Lucinda (ELSEVIER SCI LTD, 2021)
Australia needs accurate vitamin D food composition data to support public health initiatives. Previously, limitations in analytical methodology have precluded development of a comprehensive database. We used liquid chromatography with triple quadrupole mass spectrometry (LC-QQQ) to analyse 149 composite samples representing 98 foods (primary samples n = 896) in duplicate for vitamin D3, 25-hydroxyvitamin D3 (25(OH)D3), vitamin D2, 25(OH)D2. The greatest concentrations of vitamin D3 were found in canned salmon and a malted chocolate drink powder (fortified); chicken eggs and chicken leg meat contained the most 25(OH)D3. Margarine (fortified) and chocolate contained the greatest concentrations of vitamin D2, with smaller amounts found in various meat products. 25(OH)D2 was detected in various foods, including meats, and was quantitated in lamb liver. These data advance knowledge of dietary vitamin D in Australia and highlight the importance of analysis of these four forms of vitamin D to accurately represent the vitamin D content of food.